Prevalence of Thyroid Function Abnormalities and Its Association with Physical Fatigue in First-Year Medical Students - Arindam Ghosh; Debdeep Dasgupta; Susumna Biswas (International Journal of Integrated Health Sciences)
Objective: To estimate prevalence and type of thyroid function abnormalities and explore their associations with physical fatigue in first-year medical students.